Greenhouse Gases Abatement by Catalytic Dry Reforming Of Methane to Syngas over Samarium Oxide-Supported cobalt Catalyst - Ayodele, Bamidele V.; Khan, Maksudur R.; Cheng, C. K. (Springer Berlin Heidelberg, 2017)
Anthropogenic activities often result in the emissions of methane (CH4) and carbon dioxide (CO2) which are the principal components of greenhouse gases. The mitigation of these gases to avert further occurrence of global warming has attracted a lot of research interest. In this study, the potential of greenhouse gases abatement via catalytic CO2 (dry) reforming of methane to syngas over samarium oxide-supported cobalt (20 wt% Co/80 wt% Sm2O3) catalyst was investigated. The 20 wt% Co/80 wt% Sm2O3 material was synthesized via wet impregnation method and characterized using different instrument techniques. The methane dry reforming reaction, as well as its kinetics over the catalyst, was studied in a stainless steel fixed-bed continuous flow reactor at feed (CH4:CO2) ratios range of 0.1–1.0, temperature range of 923–1023 K and gas hourly space velocity (GHSV) of 30,000 h−1. The 20 wt% Co/80 wt% Sm2O3 catalyst showed promising catalytic activity evident from the highest CH4 and CO2 conversion of ~71 and ~74% as well as the highest hydrogen (H2) and carbon monoxide (CO) yield of ~62 and ~73%, respectively. Moreover, the methane dry reforming over the 20 wt% Co/80 wt% Sm2O3 catalyst produces H2/CO ratio close to unity hence suitable for use as a chemical intermediate for synthesis of oxygenated fuels. The kinetic data obtained from the methane dry reforming were fitted to power law model. Apparent activation energies of 88.62, 80.12, 108.12 and 100.91 kJ mol−1 were obtained for CH4, CO2, H2 and CO, respectively. The characterization of the spent 20 wt% Co/80 wt% Sm2O3 catalyst after 4 h of time-on-stream has confirmed the presence of amorphous carbon which can easily be gasified.